The use of logical connectors in the academic writing of Macedonian learners of English - Stojanovska-Ilievska, Nataša (Vestnik za tuje jezike, 2018)
This paper explores the use of English logical connectors in the academic writing of Macedonian learners of English. In this paper, logical connectors are defined as types of cohesive devices "that may add little or no propositional content by themselves, but that serve to specify the relationships among sentences in oral and written discourse" (Celce-Murcia and Larsen-Freeman, 1999: 519). The paper is based on a study carried out among Macedonian second-year university students of English who attend Academic Writing classes as part of the curriculum. More specifically, the study focuses on the following subtypes of logical connectors: additive, adversative, causal and temporal. It aims to determine the frequency of logical connectors, their distribution across the four categories, as well as the appropriateness of their use in a given context. The paper discusses the research findings and investigates the possible reasons for the (in)frequent use of specific logical connectors. These results are then placed in the context of similar studies conducted on non-native and native academic writing in English and finally, the pedagogical implications of the study are discussed.
Keywords: akademsko pisanje; analiza diskurza; angleščina; korpusna študija; logični konektorji; makedonski učenci; pisno izražanje